Mechanical properties of selected granitoids along the Karora hydropower project, Besham, Northern Pakistan: Insights from petrography and joint analysis - Khan, Musa; Li, Huan; Khan, Asad; Hussain, Waqas; Khan, Rehan; Ali, Rashid (Frontiers in Earth Science, 2023)
The stability of tunnel site depends upon the deformation behaviors of the surrounding rocks, including joint density, mineral composition, micro cracks, and grain boundaries. The aim of this study was to analyze the mechanical properties of the Besham Complex in Northern Pakistan in terms of petrography and joint analysis. The Besham complex is prone to deformation as it is bounded by the Main Mantle Thrust (MMT) in the north, the Thakot fault (Tf) in the east, and the Swat block in the west. In the study area, the deformation was observed at the mesoscopic scale, while alteration in grains and fractures were determined at a microscopic scale. Detailed petrographic study of the representative samples from each station revealed that the area is dominantly composed of granite, quartz syenite, quartz monzonite, granodiorite, quartz-rich granitoid, monzogranite, alkali feldspar granite, and quartz monzodiorite. Extensive field work was performed to determine the joint volume (JV), in which the number of joints per cubic meter was recorded for each joint set. The rock quality designation (RQD) was calculated through JV analysis. An RQD value <25% suggested that most rocks are very poor quality, while samples with RQD values between 25% and 50% are poor quality. The petrographic analysis revealed that the dominant contents of the rock samples are feldspar (55.6%), quartz (27%), and mica (17.4%). Petrographic control over surface joint volume was established, suggesting that abundant feldspar, coarse grain, anhedral to subhedral grain shape, microcracks, and alteration of minerals provide planes of weakness for joints and thus reduce the RQD value. Therefore, some serious precautions and supporting measurements, such as shotcrete, rock bolts, metal mesh, and steel arch supports, are essential to avoid severe geo-hazards during further excavation.